Evaluation of Abnormal Radiological Findings in Children Under Five Years With Acute Pyelonephritis: A Retrospective Cohort Study - Parvaresh, Saeedeh; Soltani Nejad, Najmeh; Shafie'ei, Mohammad (Journal of Pediatric Nephrology, 2022)
Background and Aim: Urinary tract infection is one of the most common infections in childhood. The disease should not be overlooked because it has long-term complications such as renal scarring and failure. We aimed to determine the relationships between radiological findings in children under five years with acute pyelonephritis and its long-term complications. Methods: In this retrospective study, we reviewed the medical records of all children hospitalized with acute pyelonephritis in a two-year period. We studied, extracted, and analyzed the imaging and demographic data of the patients. Results: Out of 210 available cases, 54 children with acute culture-positive pyelonephritis were included. All the included cases had undergone ultrasound, Radionuclide Cystogram (RNC), Voiding Cystourethrography (VCUG) (for urinary reflux), and late DMSA (Dimercaptosuccinic Acid) scintigraphy. We found that 46.2% had Vesicoureteral Reflux (VUR), and 57.4% had an abnormal ultrasound, with hydronephrosis being the most common finding (74.1%). We also found a significant correlation between ultrasound and VUR (P=0.002). About 37% also had abnormal DMSA scintigraphy. However, in those with normal ultrasound results, 20% suffered from VUR, with one being severe. Seven cases also had abnormal DMSA scintigraphy. Conclusion: We demonstrated that a normal urinary ultrasound does not rule out the possibility of VUR or the risk of progression to renal parenchymal dysfunction and scarring. Therefore, we suggest further utilizing the available radiologic techniques to diagnose and minimize subsequent renal complications in the disease promptly.